Exploring the Antidiarrheal Properties of Papaya Leaf: Insights In Vivo Study in Mice-Model and In Silico Analysis at M3 Muscarinic Acetylcholine Receptor Interaction - Nyi Mekar Saptarini; Faruk Jayanto Kelutur; Mary Jho-Anne Tolentino Corpuz (Scientifica)
Diarrhea caused by gut motility involves 5-HT3 serotonin receptor (5-HT3R) antagonist, M3 muscarinic acetylcholine receptor (M3-AchR), and H1 histamine receptor (H1R) via their respective agonist. Papaya (Carica papaya L.) leaf is an herbal medicine to treat diarrhea in Indonesia, though this has not yet been proven scientifically. This study aimed to determine the antidiarrheal properties of papaya leaf through in vivo and in silico studies. In the mice model, papaya leaves were infused with distilled water and subjected to in vivo antidiarrheal study using castor oil-induced diarrhea. In silico molecular docking study of nineteen secondary metabolites was carried out on the M3-AchR (PDB ID: 5ZHP) using AutoDock Tools 1.5.6, while ADMET was predicted by pre-ADMET. The results showed that papaya leaf infusion caused a decrease in the total number of feces, an increase in the onset time of diarrhea, a reduction in the frequency of diarrhea, and an increase in the percentage of inhibition of diarrhea. Quercetin 3-rutinoside, a flavonoid glycoside, is potentially an antidiarrheal remedy at M3-AchR. ADMET prediction showed good distribution on the target and was not toxic, but absorption needed to be considered. We concluded that the antidiarrheal activity of papaya leaf infusion was dose-dependent. Based on a molecular docking study, the flavonoid glycoside was very effective as an antidiarrheal remedy. ADMET prediction showed a specific distribution to the target and was not toxic.